Neurotrophic factors combined with stem cells in the treatment of sciatic nerve injury in rats: a meta-analysis. Issue 1 (28th January 2022) - Liu, Kuang-Pin; Ma, Wei; Li, Chun-Yan; Li, Li-Yan
Abstract: Treatment of peripheral nerve regeneration with stem cells (SCs) alone has some limitations. For this reason, we evaluate the efficacy of neurotrophic factors combined with stem cell transplantation in the treatment of sciatic nerve injury (SNI) in rats. PubMed, Cochrane Library, Embase, WanFang, VIP and China National Knowledge Infrastructure databases were retrieved from inception to October 2021, and control experiments on neurotrophic factors combined with stem cells in the treatment of SNI in rats were searched. Nine articles and 551 rats were included in the meta-analysis. The results of meta-analysis confirmed that neurotrophic factor combined with stem cells for the treatment of SNI yielded more effective repair than normal rats with regard to sciatic nerve index, electrophysiological detection index, electron microscope observation index, and recovery rate of muscle wet weight. The conclusion is that neurotrophic factor combined with stem cells is more conducive to peripheral nerve regeneration and functional recovery than stem cells alone. However, due to the limitation of the quality of the included literature, the above conclusions need to be verified by randomized controlled experiments with higher quality and larger samples.